Analysis of Deauthentication Attack on IEEE 802.11 Connectivity Based on IoT Technology Using External Penetration Test - Kristiyanto, Yogi; Ernastuti, Ernastuti (Bina Nusantara University, 2020)
The research aims to know the level of security of WiFi connectivity against deauthentication attacks on Internet of Things (IoT)-based devices. It is done through testing using an external penetration test method. The external penetration test simulates a real external attack without information about the target system and network given. The process starts from accessing the device through Internet or WiFi by the test target. At the same time, the attacker performs Denial-of-Service (DoS) attacks onWiFi. The attacker uses Arduino ESP8266 NodeMCU WiFi with Lua programming. To record WiFi activities, the researchers use CommView for WiFi V. 7.0, and the target is Internet Protocol (IP) camera device. The result shows that the communication of the test target with the gateway is lost, but the Media Access Control (MAC) of the test target is still registered at the gateway. Deauthentication attacks cause communication paralysis, and several changes occur, such as an increase in data rate, and change in frequency channel, Distribution System (DS) status, retry bits in frame management, and the sequence number.